Parental Access to Healthcare following Paediatric Surgery-The Precarious Role of Parents as Providers of Care in the Home - Stefan Nilsson; Mia Hylén; Inger Kristensson-Hallström; Gudrún Kristjánsdóttir; Pernilla Stenström; Runar Vilhjálmsson (MDPI AG, 2023)
Access to healthcare can facilitate parents' self-management of their children's care. Healthcare access can be described as consisting of six dimensions: approachability, acceptability, affordability, availability, appropriateness, and aperture. The aim of this study was to analyse these dimensions of healthcare access experienced by parents caring for their children at home following paediatric surgery. The method-directed content analysis, conducted with the six-dimensional framework of access to healthcare as a guide, was used to analyse twenty-two interviews with parents of children treated with paediatric surgery. All six dimensions were represented in the results. Acceptability was the most frequent dimension, followed by appropriateness and approachability. Affordability, availability, and aperture were less represented. Although access to healthcare after paediatric surgery is generally appropriate and approachable, parents may experience insecurity in performing the self-management needed. Complementary forms of information provision, e.g., telemedicine, can be valuable in this regard.